(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
The current study investigated the role of multidimensional factors including psychological, social and school related that promote refusal of school attitude in middle school students. Main objectives included exploring relationship between school refusal behaviors and bullying as an institutional factor and compare gender differences. Using quantitative approach, a correlational study design was used. A survey was carried out among a sample selected by convenient sampling comprising of 200 boys and girls (100 each) of middle school (aged 11-14 years) studying in grades 6-8 in four private and public school in Rawalpindi and Islamabad. Structured questionnaires including SRAS-R, IBS and DASS were utilized to measure experience of bullying, school refusal and mental symptoms. It was hypothesized that i) the higher the experience of bullying and psychological distress, higher will be school refusal ii) boys will score higher on IBS, DASS and SRAS-R as compared to girls. Statistical analysis reveals that hypotheses were accepted and it was found that bullying is strongly associated with school refusal. Boys reported more bullying incidence as compared to girls. However, they did not vary in school refusal behavior. The information from this research can aid education and curriculum planners for managing SRB by formulating techniques of intervention based on evidence